Effect of Second Language Proficiency on Inhibitory Control in the Simon Task: An fMRI Study - Jia, Fanlu (Frontiers in Psychology, 2022)
How learning a second language (L2) changes our brain has been an important but unsolved question in neuroscience. Previous neuroimaging studies with different ages and language pairs spoken by bilinguals have consistently shown plastic changes in brain systems supporting executive control. One hypothesis posits that L2 experience-induced neural changes are associated with advantages in cognitive control, which is responsible for the selection of a target language and minimization of interference from a non-target language. However, it remains poorly understood as to whether such cognitive advantage is reflected as stronger controlled processing or increased automatic inhibition processing. In this study, using functional MRI we scanned 27 Chinese-English late bilinguals while they performed a Simon task. Results showed that bilinguals with higher L2 proficiency performed better in the Simon task, and more importantly, higher L2 proficiency was associated with weaker activation of brain regions that support more general cognitive control, including the right anterior cingulate cortex, left insula and left superior temporal gyrus. These results suggest that L2 experience may lead to a more automatic and efficient processing in the inhibitory control task. Our finding provides an insight into neural activity changes associated with inhibitory control as a function of L2 proficiency.